Knowledge, attitude, and practice of adolescents and parents toward malocclusion and orthodontic treatment - Dongni Liu; Hongbin Li (Scientific Reports)
Abstract Malocclusion is the misalignment of teeth and jaws, affecting oral health and appearance. This study aimed to examine the knowledge, attitude, and practice (KAP) of both adolescents and parents toward malocclusion. This web-based cross-sectional study was conducted at Tianjin between July 2019 and July 2022, enrolled adolescents and their parents. The structural equation model (SEM) was used to analyze the interactions between KAP. A total of 478 adolescents and 380 parents were included. For knowledge, the scores were 6.95 ± 2.69 for adolescents and 7.07 ± 2.90 for parents (possible range, 0–12). For attitude, the scores were 36.96 ± 7.86 for adolescents and 33.26 ± 9.20 for parents (possible range, 13–65). For practice, the scores were 39.88 ± 7.85 for adolescents and 25.75 ± 8.56 for parents (possible range, 11–55). In parents, knowledge, practice, being a service personnel and production personnel, and acquiring knowledge through the Internet were associated with receiving orthodontic treatment. The SEM showed that knowledge directly affected attitudes (β = 0.551, P < 0.001) and practices (β = 1.122, P < 0.001). But attitudes did not affect practices (β=-0.003, P = 0.923). Adolescents and parents demonstrate unsatisfactory levels of knowledge, attitudes, and practices toward malocclusion. Improvements can be made by focusing on enhancing knowledge and encouraging proactive practices.